2022
DOI: 10.21203/rs.3.rs-1588901/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of cranberry powder on the diversity of microbial communities and quality characteristics of fermented sausage

Abstract: Fermented sausage is popular with many consumers because of its distinctive flavor, but the safety of it has attracted widespread attention. At present, nitrite is widely used in fermented meat products because of its ideal color and bacteriostatic effect, but nitrite can be transformed into nitrosamines, which cause strong carcinogenic effects. Therefore, it is urgent to actively explore safe and efficient nitrite substitutes. In this study, cranberry powder was selected as a natural substitute for nitrite du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They used cranberry powder as a natural alternative to nitrite. The results proved that cranberry powder could improve the color, flavor, and microbial safety of fermented sausages (Yang et al, 2022). Xi et al studied the effect of natural antimicrobials to improve the control of Listeria monocytogenes in cured cooked meat.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They used cranberry powder as a natural alternative to nitrite. The results proved that cranberry powder could improve the color, flavor, and microbial safety of fermented sausages (Yang et al, 2022). Xi et al studied the effect of natural antimicrobials to improve the control of Listeria monocytogenes in cured cooked meat.…”
Section: Introductionmentioning
confidence: 97%
“…The cranberry powder extracted from the fruit has a bright red color and is known to contain various classes of polyphenolic compounds. Yang et al (2022) showed the effect of cranberry powder on microbial diversity and quality characteristics of fermented sausages. They used cranberry powder as a natural alternative to nitrite.…”
Section: Introductionmentioning
confidence: 99%